ENHANCING THE LEGAL FRAMEWORK FOR SUSTAINABLE PUBLIC PROCUREMENT: A COMPREHENSIVE SUSTAINABLE DEVELOPMENT PLAN FOR INDONESIA (UUM Journal of Legal Studies, 2024)
The concept of “sustainable public procurement” has emerged worldwide. It instructs governments to prioritize sustainability throughout the procurement process in the economic, social, and environmental aspects. Such a concept is significant as the government has an enormous purchasing power to stimulate the market. Nonetheless, past empirical research indicates that in the context of Indonesia, the country has not addressed several vital issues on sustainable public procurement despite the worsening environmental degradation. There have been no specific guidelines and capacitybuilding system established for government officers. Therefore, this paper aims to discuss this problem from the perspective of law and suggest the necessary improvements in the legal framework, utilizing normative legal research methods focusing on the applicable laws. Through a comparative approach, using statutes and conceptual frameworks, this study examines the Indonesian current legal instruments governing sustainable public procurement. Several other countries will be used as exemplars of best practices. This research finds that the legal framework of sustainable public procurement in Indonesia is relatively inadequate compared to other countries, particularly regarding guidelines for implementation and institutional cooperation. In addition to its Presidential Regulation Number 12 of 2021, Indonesia should strengthen the planning, monitoring, and enforcement mechanisms through strategic overarching plans and further regulations to foster the effective implementation of a system of sustainable public procurement.